Alternative stable conformation capable of protein misinteraction links tRNA synthetase to peripheral neuropathy. Issue 13 (22nd May 2017) - Blocquel, David; Li, Sheng; Wei, Na; Daub, Herwin; Sajish, Mathew; Erfurth, Maria-Luise; Kooi, Grace; Zhou, Jiadong; Bai, Ge; Schimmel, Paul; Jordanova, Albena; Yang, Xiang-Lei
Abstract: While having multiple aminoacyl-tRNA synthetases implicated in Charcot-Marie-Tooth (CMT) disease suggests a common mechanism, a defect in enzymatic activity is not shared among the CMT-causing mutants. Protein misfolding is a common hypothesis underlying the development of many neurological diseases. Its process usually involves an initial reduction in protein stability and then the subsequent oligomerization and aggregation. Here, we study the structural effect of three CMT-causing mutations in tyrosyl-tRNA synthetase (TyrRS or YARS ). Through various approaches, we found that the mutations do not induce changes in protein secondary structures, or shared effects on oligomerization state and stability. However, all mutations provide access to a surface masked in the wild-type enzyme, and that access correlates with protein misinteraction. With recent data on another CMT-linked tRNA synthetase, we suggest that an inherent plasticity, engendering the formation of alternative stable conformations capable of aberrant interactions, links the tRNA synthetase family to CMT.